2015
DOI: 10.1007/978-3-319-16555-4_11
|View full text |Cite
|
Sign up to set email alerts
|

Engineering the Nanoparticle-Protein Interface for Cancer Therapeutics

Abstract: Intracellular delivery of functional proteins using nanoparticles can be a game-changing approach for cancer therapy. However, cytosolic release of functional protein is still a major challenge. In addition, formation of protein corona on the surface of the nanoparticles can also alter the behavior of the nanoparticles. Here, we will review recent strategies for protein delivery into the cell. Finally we will discuss the issue of protein corona formation in light of nanoparticle-protein interactions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 125 publications
(130 reference statements)
0
14
0
1
Order By: Relevance
“…Additionally, more work is needed to ensure predictable biological and in vivo outcomes (Azhdarzadeh et al, 2015a; Mahon et al, 2012). Should this goal be accomplished, it could potentially revolutionize multiple therapeutic areas and make significant improvements in nanomedicine (Saie et al, 2015). …”
Section: Challenges Of the Protein Coronamentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, more work is needed to ensure predictable biological and in vivo outcomes (Azhdarzadeh et al, 2015a; Mahon et al, 2012). Should this goal be accomplished, it could potentially revolutionize multiple therapeutic areas and make significant improvements in nanomedicine (Saie et al, 2015). …”
Section: Challenges Of the Protein Coronamentioning
confidence: 99%
“…In the presence of the corona, cells are protected from the damaging effects that the bare nanoparticle surface can engender until the nanoparticles and protein corona are cleared through phagocytosis (Wang et al, 2013). Understanding these fundamental processes are essential as the unique combination of the nano-bio interphase directs the nature of a corona, which then determines the biological identity of the protein corona-nanoparticle complex (Saie et al, 2015; Jiang et al, 2010). …”
Section: Introductionmentioning
confidence: 99%
“…The formation of protein corona has been experimentally interpreted as competitive adsorption and desorption of plasma proteins on particle surfaces, called the Vroman effect . Lundqvist et al found that the adsorption of proteins onto polystyrene (PS) nanoparticles is modulated by particle size and surface properties, which is rationalized by van der Waals, electrostatic and hydrophobic interactions . Among those forces, the hydrophobic interaction has been considered as a key factor for protein adsorption .…”
Section: Introductionmentioning
confidence: 99%
“…Our previous research on nano/micro-particle systems composed of HAp coated with the chitosan-poly(D,L)-lactide-co-glycolide polymer blend (HAp/Ch-PLGA) has justified the use of HAp as a core component of composite drug carriers for organ-targeting therapies [19]. Along with the particle size, shape and composition, the fate of particles injected into the bloodstream is mainly defined by the type and the structure of proteins bound to them [20, 21], which can be controlled by tailoring the composition, the topography and the charge distribution on the particle surface. Coating HAp nanoparticles with different polymers has correspondingly directed HAp to different organs [19].…”
Section: Introductionmentioning
confidence: 99%